A Few Remarks on behalf of the rehabilitation of the forgotten filiation of Stephen Nemanja - Szefliński, Błażej (Balcanica Posnaniensia. Acta et studia, 2016)
Contemporary historians agree that the father of grand prince Stephen Nemanja was Zavida. This opinion is based on the comparison of genealogical data from different sources. The data, however, is not as unequivocal as it is supposed to be. The close analysis of the account of Ansbert, the chronicler of the third crusade, suggests a different understanding of some of the data. It should be admitted that the discussion concerning the identity of Nemanja’s father was closed too early. The seals of Nemanja and his brother Stracimir prove beyond doubt that both brothers had the same name Stephen. Most probably they inherited the same names from their father. Even though already at the end of 1980s Jan Leśny in one of his works mentioned this fact, it still has not been properly explored in historiography. However, this observation lets us assume that Nemanja’s father could be Stephen Vukan, known only from reference made by Anna Komnene. Such a filiation has been already presented but on the basis of wrong premises. Now it receives a deserved recognition.